De novo transcriptome characterization of Vitis vinifera cv. Corvina unveils varietal diversity - Venturini Luca (BMC Genomics, 2013)
Abstract Background Plants such as grapevine (Vitis spp.) display significant inter-cultivar genetic and phenotypic variation. The genetic components underlying phenotypic diversity in grapevine must be understood in order to disentangle genetic and environmental factors. Results We have shown that cDNA sequencing by RNA-seq is a robust approach for the characterization of varietal diversity between a local grapevine cultivar (Corvina) and the PN40024 reference genome. We detected 15,161 known genes including 9463 with novel splice isoforms, and identified 2321 potentially novel protein-coding genes in non-annotated or unassembled regions of the reference genome. We also discovered 180 apparent private genes in the Corvina genome which were missing from the reference genome. Conclusions The de novo assembly approach allowed a substantial amount of the Corvina transcriptome to be reconstructed, improving known gene annotations by robustly defining gene structures, annotating splice isoforms and detecting genes without annotations. The private genes we discovered are likely to be nonessential but could influence certain cultivar-specific characteristics. Therefore, the application of de novo transcriptome assembly should not be restricted to species lacking a reference genome because it can also improve existing reference genome annotations and identify novel, cultivar-specific genes.